Perancangan User Experience untuk Learning Management System pada Siswa SMA di Sekolah Indonesia Kuala Lumpur menggunakan Metode Human-Centered Design - Nabila Khaerunisa Thazila; Retno Indah Rokhmawati; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The spread of the virus Corona at the end of December 2019 throughout the world caused a pandemic. This then affects various fields, one of which is education. Senior High School at Sekolah Indonesia Kuala Lumpur conducts distance learning through several platforms. This is quite helpful for teachers and students in conducting learning remotely, but there are some obstacles for teachers and students in using the platform for online learning. Based on this, this study aims to design a user experience that can help overcome the problems faced by teachers and students at the Kuala Lumpur Indonesian School related to the obstacles experienced by teachers and students by designing a Learning Management System (LMS). The LMS design uses the Human Centered Design method because this method is an interactive design approach and focuses on the use of the human side. This study resulted in the design of the website Kuala Lumpur Indonesian School LMSin the form of a high-fidelity prototype and tested using usability testing with user satisfaction measurements using the User Experience Questionnaire (UEQ) which was used to determine the suitability of the design made with user needs. The results of the User Experience Questionnaire (UEQ) test, namely the Learning Management System of the Indonesian School of Kuala Lumpur, have an average value that is in the positive category with an average value range of 1,650 - 2,475 and the entire scale is in the excellent category and the efficiency scale are in the good category. The results of the evaluation that have been carried out have produced several problems so that improvements are made which result in three recommendations for improvement for the Learning Management System for the Indonesian School of Kuala Lumpur.